Long-term outcomes of COVID-19 infection in patients with solid tumors - Ünsal, Oktay; Yazıcı, Ozan; Özkan, Ömer Faruk; Savaş, Gözde; Yıldırım Özdemir, Nuriye; Üner, Aytuğ; Günel, Nazan; Özet, Ahmet (The European Research Journal, 2023)
Objectives: We analyzed the impact of some clinical and disease-specific factors on the longterm outcomes of SARS-CoV-2 infection in patients with solid tumors. Methods: Total of 739 patients with known solid malignancy and infected by SARS-CoV-2 before the beginning of vaccination were examined. Results: Seventy-six cancer patients died from COVID-19 infection-related effects such as mostly pulmonary and cardiovascular system disorders after a median 16-month follow-up (67.1% and 14.5%; respectively). Compared with survivors (n = 468), non-survivors due to COVID-19 infection related effects (n = 76) were more likely to be aged ≥ 65 years and diagnosis with lung cancer (p = 0.01). Also, female patients were at decreased risk of mortality [OR: 0.34 (95% CI: 0.18-0.65)]. Furthermore, patients with tumor stage IV, active/stable/progressive disease and patients receiving active anticancer therapy were at increased risk of mortality (p = 0.01). Conclusions: The patients with aged ≥ 65 years, diagnosed with lung cancer, receiving active anticancer therapy, with active/stable/progressive and advanced cancer stage were at increased risk of mortality from COVID-19 infection in long-term follow-up.